Ameliorative effect of alpha lipoic acid on CCL4 induced kidney damage of male albino rats (Funded Work) - DR. SHARABANI PRADHAN; DR. SUCHISMITA ROY; DR. KOUSHIK DAS; DR. DILIP KUMAR NANDI (International Journal of Pharma and Bio Sciences, 2019)
The present study is done to determine the possible protective effect of alpha lipoic acid on carbon tetrachloride (CCl4) induced renal injuries in rats. The study was conducted on thirty male rats dividing into five equal groups and observe the development and extent of renal injuries in rats by histopathological and biochemical changes. Results obtained from the present study showed that CCl4 treatment can results significant increase in plasma urea, creatinine and MDA level and significant reduction in antioxidant enzyme activities like SOD, Catalase in plasma and kidney tissues. Oral co administration of alpha lipoic acid at three different doses attenuated the adverse changes. From histopathological studies it had been observed that the kidney tissue section of untreated control group showed normal histoarchitecture, CCl4 treated showed severe degeneration of kidney cell. Oral co-administration of alpha lipoic acid showed comparatively well-organized glomerulus and tubules than other lower dose group. Conclusions: It has been concluded that alpha lipoic acid in high doses like (100 and 200 mg/ kg body weight/ day) had shown similar r protective effect against CCl4 induced renal damage in rats than other lower dose group (50 mg/kg body weight) due to its strong antioxidative properties.